Aplikasi Sirkulasi Fungsional pada Interior Shopping Mall âTunjungan Plazaâ di Surabaya - Sriti Mayang Sari, Melisa Lusiana (Intra, 2014)
ââTunjungan Plazaâ is the largest and most popular shopping mall in Surabaya, consists of 4 main buildings (âTunjungan Plazaâ 1-4) and connected through circulation spaces. Circulation is an element that organizes and connects different part of the shopping mall, such as shops, anchor tenant and other mall facilities. Consideration of organizing circulation can be separately identified into functional and qualitative requirements. The functional requirements are primary building planning considerations that represent the basic and well established general rules of shopping mall planning, and the qualitative requirements are recommended secondary planning that tends towards the consideration of the use of the mall from the viewpoint of the customer and are recommended considerations that can make the difference between one mall and another. The aim of this research is to find out the functional circulation application in âTunjungan Plazaâ. The result is âTunjungan Plazaâ applies functional circulation requirements according to the parameters, even there are some applications that are not matching the parameters.